Recovery of nonpolio enteroviruses from l20b cell line with non-reproducible cytopathic effect (2018)
Background and Aim of the Study: Samples showing cytopathic effect (CPE) on initial inoculation into L20B cell line but with no observed or reproducible CPE on passage in L20B or RD are considered negative for both poliovirus and nonpolio enteroviruses (NPEVs). The phenomenon is termed ‘non-reproducible CPE’. Its occurrence is usually ascribed to the likely presence of reoviruses, adenoviruses and other non-enteroviruses. This study aimed to investigate the likelihood that NPEVs are also present in cases with non-reproducible CPE. Place and Duration of Study: This study was carried out in the Department of Virology, College of Medicine, University of Ibadan using twenty-six (26) cell culture suspensions collected from the WHO National Polio Laboratory, Department of Virology, College of Medicine, University of Ibadan. The suspensions emanated from 13 L20B cell culture tubes that showed cytopathology within 5 days of inoculation with faecal suspension from AFP cases. However, on passage into one each of RD and L20B cell lines, the CPE was not reproducible. The study lasted for three (3) months from samples collection to report writing. Methodology: All samples were subjected to RNA extraction, cDNA synthesis, the WHO recommended VP1 RT-seminested PCR assay, species resolution PCR assay, sequencing andphylogenetic analysis. Results: Six (6) samples were positive for the VP1 RT-seminested PCR assay. Only four of which were positive by the species resolution PCR assay. The four amplicons were sequenced, however, only three (3) were successfully identified as Coxsackievirus A20 (2 isolates) and Echovirus 29 (1isolate). Conclusion: The results of this study unambiguously showed the presence of NPEVs (particularly CVA20 and E29) in cell culture supernatants of samples with CPE on initial inoculation into L20B cell line but with no observed or reproducible CPE on passage in RD cell line. Therefore, like reoviruses, adenoviruses and other non-enteroviruses, NPEVs can also be recovered in cases with non-reproducible CPE.